Clinical presentation and outcomes following posterior segment IOFB - Harsha Bhattacharjee; Satyen Deka; Manab Jyoti Barman; Ronel Soibam; Sumita S Barthakur; Lokesh Jain (Delhi Journal of Ophthalmology)
Purpose: To review the clinical features, causes of injury, types of foreign bodies, results of vitrectomy and prognostic factors in patients with posterior segment intraocular foreign bodies (IOFB). Methods: Study design: Retrospective review of clinical records. Study participants: 108 consecutive patients with posterior segment IOFB presenting at the study hospital between 1994 and 2007; and treated with IOFB removal by intraocular forceps or electromagnet or combination of the two following vitrectomy. Outcome measures: Clinical presentations, investigations, surgical techniques, final anatomical and visual status and duration of follow up. Statistical analysis: Chi-squared test. Results: The commonest presenting feature was uniocular visual loss. Work place injuries while chiseling and hammering (67.5%, n=73) without protective eyewear were the commonest. Metallic IOFBs were significantly common at 77.16% (n=98). IOFBs were removed using intraocular magnet (74%, n=80), intraocular forceps (18.5%, n=20) or a combination of the two (7.4%, n=8). Final visual acuity of ≥20/120 was achieved in 32.4% (n=35) cases. Presence of Relative Afferent Pupillary Defect (RAPD) (p<0.001), posterior segment haemorrhage (p<0.001) and Retinal Detachment (RD) (p=0.045) at presentation implied bad prognosis. Conclusions: IOFBs were mostly occupational and preventable. Cases presenting with RAPD, posterior segment haemorrhage and RD had bad visual prognosis.